(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
This article explores the importance of developing independent thinking skills in primary school students in English classes and offers innovative ways to achieve this goal. By including inquiry-based education, problem-solving activities, cooperative education, Socratic interrogation, reflective journals, creative expression, technology integration, and actual assessment, teachers can create a stimulating environment that develops critical thinking, creativity, and decision-making skills. Young readers.